Evaluasi Kapabilitas Proses Pengembangan Aplikasi Di Dinas Komunikasi dan Informatika Kota Malang Dengan Pedoman CMMI - DEV 1.3 - Ikrima Amanda Wulandari; Admaja Dwi Herlambang; Widhy Hayuhardhika Nugraha Putra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
To realize the dream of Malang City as a Smart City, Dinas Komunikasi dan Informatika (Kominfo) Kota Malang is currently in the process of fixing all the deficiencies based on the results of an evaluation of the Electronic Based Government System (EBGS) in 2018, such as developing, improving and quality improvement of existing services. However, during the application development process, there are differences or problems found and the solution of these problems has not been well documented so that it can have an impact on the further suboptimal application development process because of repeating the same mistakes. The purpose of this study is to analyze the results of the assessment of the capability level of the application development process of Malang City Communication and Information Office. The purpose of this study is to obtain data in the field through interviews and document searches. The assessment is carried out in six process areas based on the Capability Maturity Model Integration (CMMI) product roadmap using the Class CMMI Appraisal Method for Process Improvement (SCAMPI) class C. The results obtained from the assessment of the six process areas are that there is no process area that meets all existing practices. In other words, the capability level of Malang City Communication and Information Agency as a whole is still at level 0 or incomplete. Based on the results of the assessment identified recommendations to meet practices that have not been done and improve the capability level of the application development process of Dinas Kominfo Kota Malang.